2020
DOI: 10.1136/bmjgh-2019-002169
|View full text |Cite
|
Sign up to set email alerts
|

Country compliance with WHO-recommended antenatal care guidelines: equity analysis of the 2015–2016 Demography and Health Survey in Myanmar

Abstract: IntroductionEarly access to adequate antenatal care (ANC) from skilled providers is crucial for detecting and preventing obstetric complications of pregnancy. We aimed to assess factors associated with the utilisation of the new WHO ANC guidelines including the recommended number, on time initiation and adequate components of ANC contacts in Myanmar.MethodsWe examined data from 2943 mothers aged 15–49 years whose most recent birth occurred in the last 5 years prior to the 2015–2016 Myanmar Demographic and Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 37 publications
(30 reference statements)
6
24
6
Order By: Relevance
“…Our study revealed that the proportion of adequately received ANC contents was 28%. This result is in line with a study conducted in LMICs ranging from 10 to 50% in Jordan, Nigeria, Nepal, Colombia, and Haiti 49 and studies in Bangladesh (22%), 20 Zambia (29%), 16 but lower than studies done in Ghana (48%), 23 Myanmar (58%), 41 Zambia (47.1%), 50 and higher than studies in Nigeria (7%), 22 twenty countries in sub-Saharan Africa (5%). 51 The slow progress towards maternal and newborn survival due to ineffective care may be attributable to the gaps between globally recommended coverage indicators measuring contacts rather than the actual content.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study revealed that the proportion of adequately received ANC contents was 28%. This result is in line with a study conducted in LMICs ranging from 10 to 50% in Jordan, Nigeria, Nepal, Colombia, and Haiti 49 and studies in Bangladesh (22%), 20 Zambia (29%), 16 but lower than studies done in Ghana (48%), 23 Myanmar (58%), 41 Zambia (47.1%), 50 and higher than studies in Nigeria (7%), 22 twenty countries in sub-Saharan Africa (5%). 51 The slow progress towards maternal and newborn survival due to ineffective care may be attributable to the gaps between globally recommended coverage indicators measuring contacts rather than the actual content.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, studies indicate that rural resident women were significantly less likely to have higher numbers of content items of ANC services. 9 , 20 , 22 , 41 Rural women have substantially less or even absent transportation infrastructure which makes access to healthcare difficult and may contribute to the difference. 52 The study also revealed long distances to health institutions and low media exposure among rural women contributed to inadequate received ANC components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of eight or more ANC contacts according to our study was 31.2% among mothers in the Nabdam district of Ghana. This prevalence is higher than previous findings from Benin (8%), Bangladesh (6%), and Myanmar (18%) [9][10][11]. The higher prevalence observed in our study be due to the free maternal healthcare policy in Ghana [19].…”
Section: Discussioncontrasting
confidence: 81%
“…However, many low-and-middle-income countries (LMIC) are neither meeting the recommended number of eight ANC contacts nor adhering to the number of contacts per trimester of pregnancy [ 7 , 8 ]. A recent study in Benin reported that 8% of pregnant women had eight or more ANC contacts with the healthcare provider [ 9 ], while other studies in Bangladesh and Myanmar reported that only 6% and 18% of pregnant women respectively, had eight or more ANC contacts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%